How public libraries deliver value online: the perception of librarians (Libellarium: journal for research in the field of information and related sciences, 2023)
Purpose. The development and usage of digital library services have accelerated. Many libraries have expanded their digital services in response to the COVID-19 pandemic. The physical locations were closed or operated with reduced capacity and libraries continued to provide services digitally. The physical locations of many libraries have reopened but the development of digital services persists. Most libraries offer a wide variety of services digitally and many libraries are expanding their digital services. It is, therefore, relevant to explore how librarians perceive the digital public library services offered at their institutions and how the digital services supplement or replace services in the physical library.Approach/methodology/design. This study presents the findings of an interview-based study with five librarians from different public libraries across Denmark.Findings. The findings show that librarians perceive the physical and digital services as means to the same end while carefully considering the content, target audience and platform when offering services to their users. They see the digital services as a critical aspect of the raison d’etre of the library and means to attract new users.Research limitations. It is important to note that this study is based on a small sample.Practical implications. The implications for digital public library services are discussed and recommendations based on this study are considered.Originality/value. While many studies have explored librarians’ perceptions of the value of public libraries, this study focuses on librarians’ perception of the value of digital libraries and how these services supplement or replace the physical library.
Keywords: Covid-19; Denmark; digital services; public libraries; value of public libraries